Multiscale carbon fibre–reinforced polymer (CFRP) composites containing carbon nanotubes with tailored interfaces - Santos, Raquel M. (2019)
Pristine and functionalized multiwalled carbon nanotubes (MWCNTs) with tailored interfaces were efficiently dispersed in an epoxy matrix using a three-roll mill and further reinforced with carbon fibres. 1.3-Dipolar cycloaddition of azomethine ylides was used for the chemical modification of MWCNTs by a solvent-free approach. The influence of different loadings and types of MWCNTs on the final properties of the epoxy matrix was studied. Moreover, the most promising formulations were selected for manufacturing of prepreg sheets. The transversal tensile properties and the interlaminar fracture toughness under mode I loading (G ) of multiscale carbon fibre–reinforced polymer (CFRP) composites were characterized. The results point out that it is not straightforward to transfer the remarkable intrinsic properties of MWCNTs to the composite level, although an overall positive trend was found. Double cantilever beam experiments showed that G of CFRP composites was improved 44% at ultralow content of functionalized MWCNTs (0.043 wt%). IC IC